2017
DOI: 10.1016/j.jiph.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Pfcrt and Pfmdr1 genes could account for the slow recovery of chloroquine sensitive Plasmodium falciparum strains in Ghana after chloroquine withdrawal

Abstract: Unlike other countries, the chloroquine resistant marker Pfcrt T76 mutant has remained fairly stable in Ghana several years after official disuse of chloroquine. Certain mutations in Pfmdr1 may potentiate Pfcrt T76, offering a possible explanation for this observation. To understand the phenomenon, the co-existence of mutations in Pfmdr1 with Pfcrt T76 in Ghanaian Plasmodium falciparum isolates was studied. The reported presence of parasites with reduced sensitivity to amodiaquine and quinine in the country wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Mutations on the Pfmdr1 gene play a pivotal role with variable parasite response to artemisinin, ACT and non-ACT, such as chloroquine, lumefantrine, primaquine, tafenoquine, piperaquine, and mefloquine [3138], due to conformational changes in the transporter protein causing decrease in intracellular drug accumulation and effect on the malaria parasite.The haplotype N86Y-Y184F-D1246Y of Pfmdr1 was reported to be susceptible to artemisinin-based combination, whereas triple mutations S1034C, N1042D and D1246Y or increased gene copy number are associated with parasite resistance to mefloquine, halofantrine and artemisinin [36]. Although this study did not assess Pfcrt mutation, there is known synergy between mutations on Pfmdr1 and Pfcrt genes [39]. Studies in Nigeria and other areas have reported reduced in vitro and in vivo response in chloroquine-resistant isolates bearing the 76T mutation correlating strongly with Pfmdr1 86Y mutation [12, 14, 16, 21, 22, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations on the Pfmdr1 gene play a pivotal role with variable parasite response to artemisinin, ACT and non-ACT, such as chloroquine, lumefantrine, primaquine, tafenoquine, piperaquine, and mefloquine [3138], due to conformational changes in the transporter protein causing decrease in intracellular drug accumulation and effect on the malaria parasite.The haplotype N86Y-Y184F-D1246Y of Pfmdr1 was reported to be susceptible to artemisinin-based combination, whereas triple mutations S1034C, N1042D and D1246Y or increased gene copy number are associated with parasite resistance to mefloquine, halofantrine and artemisinin [36]. Although this study did not assess Pfcrt mutation, there is known synergy between mutations on Pfmdr1 and Pfcrt genes [39]. Studies in Nigeria and other areas have reported reduced in vitro and in vivo response in chloroquine-resistant isolates bearing the 76T mutation correlating strongly with Pfmdr1 86Y mutation [12, 14, 16, 21, 22, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that CQ resistance markers have reduced to a significant level compared to the previous report from the region [35]. Although the steady decline for Pfcrt T76 and Pfmdr1 Y86 has been very slow especially at regional capital (Cape Coast) of Central Region of Ghana yet the expansion of the CQ sensitive P. falciparum strains have increased appreciably [12,15,27]. Similar findings on the reappearance of CQ sensitive parasites have been reported in Malawi, Cameroon, Ethiopia, Nigeria, Tanzania and Mozambique [9,10].…”
Section: Discussionmentioning
confidence: 66%
“…An archived Plasmodium falciparum infected blood blot samples from Cape Coast, Elmina, Twifo Praso and Assin Foso were used from for this study [27]. The air-dried blood spots in zip-locked plastic envelopes containing silica gel stored at -20°C in the Department of Biomedical Sciences, University of Cape Coast were extracted using chelex extraction method.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Altogether, about two-thirds (69.2%; 18/26) of the isolates that carried the pfmdr1 86Y mutation were also found to be carrying the pfcrt 76T mutation. The pfmdr1 86Y point mutation is the second most important molecular marker of CQ resistance after pfcrt 76T, and several studies have suggested that there may be a synergistic association between these pfcrt and pfmdr1 point mutations 31,32 . Moreover, a remarkable decline in the prevalence of mutant pfcrt 76T and pfmdr1 86Y alleles has also been observed in low malaria transmission settings where drug pressure is likely to be lower 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is different from that reported in 2012, where 66% and 31% of the examined isolates carried the single NFSN and double YFSN haplotypes while only 3% carried the wild NYSN haplotype (codon 1246 was not involved) 26 . Studies from other countries such as Yemen and Ghana have reported up to ve different haplotypes 32,36 .…”
Section: Discussionmentioning
confidence: 99%